Distinct Roles of Adenosine Deaminase Isoenzymes ADA1 and ADA2: A Pan-Cancer Analysis - Gao, Zhao-wei; Yang, Lan; Liu, Chong; Wang, Xi; Guo, Wen-tao; Zhang, Hui-zhong; Dong, Ke (Frontiers in Immunology, 2022)
Objective: Adenosine deaminase (ADA) plays an important role in immune response, which includes two isoenzymes: ADA1 and ADA2. This study aims to explore the roles of ADA1 and ADA2 in cancers. Methods: HPA and GEPIA2 database were used to analyze the mRNA expression of ADA1 and ADA2 in human normal cells and tumor tissues. Enzyme assay was used to detect the ADA1 and ADA2 activities in serum from cancer patients. Kaplan-Meier (KM) plotter was used to analyze the prognostic value of ADA1 and ADA2. TIMER2.0 was used to explore how ADA1 and ADA2 correlating with immune infiltration and immune checkpoints. cBioPortal database was used to investigate the mutations of ADA1 and ADA2. LinkedOmics was used to screen the ADA1 and ADA2 expression related genes. Results：ADA1 was significant increased in several tumor tissues, including CHOL, DLBC, HNSC, KIRC, OV, PAAD, THYM and UCS. ADA2 expression was significant increased in ESCA, GBM, LAML, OV, PAAD, Skin SKCM and STAD. There were no significant changes for serum ADA1 activities in most of cancers, while serum ADA2 activities were increased in most of cancers. For prognosis, high ADA1 was associated with the poor survival of several cancers, including ESCC, HNSC , KIRC, KIRP, LIHC, LUAD and UCEC. However, high ADA2 expression showed a favorable prognosis in BRCA, CESC, HNSC, KIRC, KIRP, LUAD, OV, PAAD, Sarcoma and THYM. ADA1 showed a moderate positive correlation with multiple infiltrating immune cells in most of cancers. ADA2 was positive correlated with B cells, CD8 T cells, Monocyte/macrophage and DCs, and was strong negative correlated with myeloid-derived suppressor cells. Function analysis showed that ADA1 expression related genes were mainly enrichment in cell division biological progression. However, ADA2 related genes were mainly association with immune response. Conclusion：Although as the isoenzymes, ADA1 and ADA2 showed the opposite prognostic value and different correlative pattern with immune infiltrating. These data demonstrated the distinct roles of ADA1 and ADA2 in cancer. ADA2 might act as a protective factor in cancer.